Risk factors of Clostridioides difficile infection in hospital: A seven years prospective study - Perić, Aneta; Milenković, Bojana; Putić, Vesna; Šuljagić, Vesna (Archives of Pharmacy, 2022)
Clostridioides difficile infection (CDI) is one of the most common healthcare-associated infections (HA) (1). The risk factors (RFs) for HA CDI in surgical and non-surgical patients are poorly investigated in countries with a limited resource healthcare system (2). The aim of the study was to investigate differences in RFs associated with HA CDI and their outcomes in surgical and non-surgical patients in Military Medical Academy (MMA). A prospective cohort study was conducted from 2011 to 2017 in MMA. Study including adult patients diagnosed with initial episode of HA CDI, while deaths within 30 days of CDI diagnosis and in-hospital mortality were also recorded.P atients hospitalized for any non-surgical illness, who developed initial HA CDI were assigned to non-surgical group, whereas those who developed initial HA CDI after surgical procedures were in surgical group. During 7-year period, from 553 patients undergoing in-hospital treatment and diagnosed with CDI, 268 (48.5%) and 285 (51.5%) were surgical and non-surgical patients, respectively. The variables associated to HA CDI in non-surgical patients were as follows: age ≥ 65 years, use of proton pump inhibitors, chemotherapy and fluoroquinolones. The variables associated with HA CDI in surgical patients were: admission to Intensive Care Unit and use of second- and third-generation cephalosporins. There were significant differences between them in 30-day mortality (15.7%vs 25.6, p=0.006) and in-hospital mortality (19.8% vs 28.1%, p=0.029). Based on obtained results, including significant differences in mortality, it can be concluded that non-surgical patients were more endangered with HA CDI than surgical ones.